Anthropological inquiry of disease, illness and sickness - Vivien W.C. Yew,; Noor Azlan Mohd Noor, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
The fundamental idea for this article is a review of the theoretical discussion among experts in biomedicine and the social sciences: Arthur Kleinman, Leon Eisenberg, Horacio Fabrega, Byron Good, and Andrew Twaddle, among others; on the concepts of disease, illness, and sickness. The main objective is to explore the conceptual distinction between the triad from the field of anthropology, particularly on how culturally defined concepts of ill health are created. It is generally argued that the complexity of different opinions on human ailment causes difficulty in providing a clear distinction between the triad for the use among medical practitioners, social scientists, and laymen community at large. In particular the analysis reveals that most signs or symptoms of distress are reflective of sufferers’ personal and cultural experiences. They are the cultural processes of illness and sickness, rather than purely understood by medical profession as disease. Additionally, the article demonstrates that with the effort of the experts of biomedicine and social sciences, clear definitions of the different concepts of disease, illness, and sickness indicate different aspects of ill health. Finally, the author focuses the discussion on a proposal to explore how the full triad can be of use amongst laymen patients, particularly in times of physician-patient interactions over ailment diagnosis.